Company Value: Within the Scope of Company Size, Leverage, Profitability, and Capital Structure - Wulandari, Tri; Mujiyati, Mujiyati (Dinasti Publisher, 2024)
This study aims to empirically examine the effect of company size, leverage, profitability, and capital structure on the value of the company. In this study using quantitative research. The Data used in this study are secondary data obtained in the form of financial statements for 2018-2022 all industrial companies listed on the Indonesia Stock Exchange (IDX) that have been audited on the IDX website (www.idx.co.id). the population in this study includes manufacturing companies in the telecommunications sub-sector listed on the IDX for the period 2018-2022. Sampling using purposive sampling method. The number of samples as many as 40 companies. Data analysis using multiple linear regression using statistical Application Program tools: Statistical Product and Service Solutions (SPSS). The results of this study is that the size of the company, and profitability does not affect the value of the company, while leverage, and capital structure affect the value of the company.